Inappropriate dose of nonvitamin-K antagonist oral anticoagulants: prevalence and impact on clinical outcome in patients with nonvalvular atrial fibrillation. Issue 10 (October 2020) - Godino, Cosmo; Bodega, Francesca; Melillo, Francesco; Rubino, Francesca; Parlati, Antonio L.M.; Cappelletti, Alberto; Mazzone, Patrizio; Mattiello, Paolo; Della Bella, Paolo; Castiglioni, Alessandro; Alfieri, Ottavio; De Bonis, Michele; et al.
Abstract : Background: Limited real-world data are available regarding the outcome of patients treated with inappropriate dose of nonvitamin-K antagonist oral anticoagulants (NOACs). Objective: To assess the prevalence and factors associated with inappropriate dose prescription of NOACs and to evaluate adverse events that come from this inappropriate prescription. Methods: Single-center multidisciplinary registry including nonvalvular atrial fibrillation patients treated with NOACs. Based on guidelines criteria for dose reduction, two subcohorts were defined as treated with appropriate or inappropriate NOACs dose. Primary efficacy endpoint was 2-year rate of thromboembolic events. Primary safety endpoint was 2-year rate of major bleeding. Event-free survival curves among groups were compared using Cox–Mantel test. Results: A total of 760 nonvalvular atrial fibrillation patients were included; 32% patients were treated with dabigatran, 34% with apixaban, 24% with rivaroxaban and 10% with edoxaban. An inappropriate dose was prescribed in 96 patients (12.6%), and in most cases (68%) it was too low. Rivaroxaban (15%) and apixaban (18.5%) were the most frequently prescribed with an inappropriate dose. Patients treated with an inappropriate dose were elderly people, with low-creatinine clearance value, who had experienced previous bleeding and with a high CHADS2 VASc score. In 2 years, a trend for higher numbers of thromboembolic events (5.2 vs. 3.3%, P  = 0.348) and less major bleeding (2.1 vs. 4.2%, P  = 0.316) has been observed in patients with inappropriate NOACs prescriptions. Conclusion: Nearly 13% of patients were treated with an inappropriate dose of NOACs, in this single-center study. A trend for higher numbers of thromboembolic events was observed in these patients. The results should be considered as hypothesis generating.